OFFSET
1,4
FORMULA
a(1) = 0; a(n) = a(n-1) + (n-1)^2 - 2 for n > 0.
a(n) = Sum_{k=1...n-1} (k^2-2) = A000330(n-1)-2*A000027(n-1) = (n-1)*(2*n^2-n-12)/6. - Christoph Pacher (christoph.pacher(AT)ait.ac.at), Jul 23 2010
G.f.: -x^2*(1-5*x+2*x^2)/(1-x)^4. - Colin Barker, Apr 04 2012
EXAMPLE
a(2) = a(1) + 1^2 - 2 = 0 + 1 - 2 = -1; a(3) = a(2) + 2^2 - 2 = -1 + 4 - 2 = 1.
MATHEMATICA
lst={0}; s=0; Do[s+=n^2 - 2; AppendTo[lst, s], {n, 5!}]; lst
Table[Sum[(i^2 + n - 1), {i, 0, n}], {n, -1, 41}] (* Zerinvary Lajos, Jul 11 2009 *)
Join[{0}, Accumulate[Range[50]^2-2]] (* Harvey P. Dale, Jul 23 2018 *)
PROG
(PARI) {a=2; for(n=0, 42, print1(a=a+n^2-2, ", "))}
CROSSREFS
KEYWORD
sign,easy
AUTHOR
Vladimir Joseph Stephan Orlovsky, Sep 30 2008
EXTENSIONS
Edited by Klaus Brockhaus, Oct 17 2008
STATUS
approved